2022
DOI: 10.1016/s2666-5247(21)00269-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and dose-sparing effect of Japanese encephalitis vaccine administered by microneedle patch in uninfected, healthy adults (MNA-J): a randomised, partly blinded, active-controlled, phase 1 trial

Abstract: Background It is unclear whether microneedle vaccinations of Japanese encephalitis virus can induce sufficient neutralising antibodies and reduce the amount of vaccine needed. We aimed to assess the safety and dose-sparing effect of a microneedle vaccine patch against Japanese encephalitis in healthy individuals who are naive to both the vaccine and natural infection. MethodsThe MNA-J study was a randomised, partly blinded, active-controlled, phase 1 clinical trial at Hokkaido University (Sapporo, Japan) that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…No risks of reuse Limited mechanical strength Limited loading capacity Limited dose accuracy Strong hygroscopicity Influenza [40] Tuberculosis [ 43,63] Subcutaneous tumor [64] Melanoma [65] Prostate cancer [66] Cervical cancer [67] HBV infection [68] COVID-19 [69] Japanese encephalitis [70] Tetanus [71] Hollow MNs Large loading capacity Controlled and accurate drug release…”
Section: No Residue Low Cost Of Fabricationmentioning
confidence: 99%
“…No risks of reuse Limited mechanical strength Limited loading capacity Limited dose accuracy Strong hygroscopicity Influenza [40] Tuberculosis [ 43,63] Subcutaneous tumor [64] Melanoma [65] Prostate cancer [66] Cervical cancer [67] HBV infection [68] COVID-19 [69] Japanese encephalitis [70] Tetanus [71] Hollow MNs Large loading capacity Controlled and accurate drug release…”
Section: No Residue Low Cost Of Fabricationmentioning
confidence: 99%
“…Additionally, the immunogenicity benefits of MAPs in humans have to date only be shown with protein-based vaccines, such as influenza 9 and an inactivated Japanese encephalitis virus vaccine. 20 In both of these cases, delivery of the vaccine by MAP resulted in enhanced immune responses compared with N&S injection. However, whether a similar effect will be seen with other vaccine types such as nucleic acids, live attenuated viruses or live virus vectors remains to be seen.…”
Section: Challenges In Making the Shift To Vaccine Maps A Commercial ...mentioning
confidence: 99%
“…As a function of this targeted vaccine delivery, our group and other researchers have demonstrated that enhanced immune responses with lower doses of vaccine are achievable as compared to traditional needle-based vaccination methods [8,9]. Previous studies have demonstrated the broad utility of the HD-MAP delivery platform, which has shown promising results against the dengue virus [10][11][12], influenza [13,14], West Nile virus, Chikungunya virus [15], Japanese encephalitis [16], and poliovirus [17,18]. Recently, pre-clinical studies using the HD-MAP have shown promising results producing broadly high titre neutralizing antibody responses against the SARS-CoV-2 ancestral virus and variants of concerns [19].…”
Section: Introductionmentioning
confidence: 97%